Burma : A Nation at the Crossroads - Rogers, Benedict (London Rider Books, 2015)
For more than 50 years, Burma has been ruled by a succession of military regimes which rank among the most oppressive dictatorships in the world. Accused of crimes against humanity, they have brutally mistreated their people. This book explains the country's conflicted history, as well as its contemporary struggle for justice.
Include Notes, Bibliography and Index